Strategic Default, Debt Structure, and Stock Returns - Valta, Philip (Journal of Financial and Quantitative Analysis, 2016)
Abstract This paper theoretically and empirically investigates how debt structure and strategic interaction among shareholders and debt holders in the event of default affect expected stock returns. The model predicts that expected stock returns are higher for firms that face high debt renegotiation difficulties and that have a large fraction of secured or convertible debt. Using a large sample of publicly traded U.S. firms for the period 1985–2012, the paper presents new evidence on the link between debt structure and stock returns that is supportive of the model’s predictions.